Cabbage Core Powder as a New Food Material for Paste Preparation with “Nata Puree” - Tokuyasu, Ken; Yamagishi, Kenji; Ando, Yasumasa; Shirai, Nobuya (Journal of applied glycoscience : JAG, 2022)
Cabbage core (CC) is regarded as a waste part of the vegetable, despite being edible and containing various nutritional and functional compounds. We investigated the properties of CC powder with particle sizes < 1 mm as a new food material. CC powder was more resistant to structural deformation than leaf-derived powder, particularly CC powder with particles ≥ 0.3 mm in size. To examine the application of CC powder in 3D printed foods, we investigated the effects of “nata puree,” a disintegrated nata de coco made with tamarind seed gum (NPTG), on paste made with CC powder. NPTG promoted stable binding of paste made using CC powder, which was successfully extruded using a syringe to form a bar with a granular structure. Thus, CC powder possesses unique textural/structural properties for its application in next-generation foods.